Causes of decadal distributions of Indian summer monsoon rainfall during the last 1500 years. (21st August 2022) - Wang, Zhiyuan; Wang, Jianglin; Shi, Xiaoyi; Jia, Jia; Yan, Mi
Abstract: Understanding the distribution of Indian summer monsoon rainfall (ISMR) and the relationships with external forcing factors (EXFs) and internal climate variability (ICV) is crucial for improving the prediction accuracy of ISMR. Here, we explore and quantify the influence of EXFs and ICV on the distribution of ISMR at decadal timescales over the past 1500 years using the Community Earth System Model (CESM). We identified the major ICV and EXF modes of ISMR distributions in simulations from 501 to 1850 ad and 1851 to 2000 ad. The results show that ICV plays a dominant role in decadal ISMR changes during the pre‐industrial and the current periods. Simulations show east–west contrasts over the Indian subcontinent, with a center of rainfall variability in the high‐latitude regions around 28°N. The EXF mode, calculated from the leading mode of the singular value decomposition analysis, exhibits a nearly uniform increase (or decrease) in the distribution of ISMR over the study region. From 501 to 1850 ad, the signals of greenhouse gases (GHGs), and land use and land cover (LULC) in the ISMR at the decadal timescale are weak and difficult to isolate from the ICV. Our numerical analyses show that natural forcing was a dominant contribution ( 64.1%) to the forced ISMR distribution. From 1851 to 2000 ad, natural forcing, GHGs and LULC all contributed to the forced ISMR distribution. GHGs represent a key external forcing factor affecting the distribution of ISMR and could explain 22.3% of the total variance. LULC and natural forcing factors contribute 17.5 and 16.4% to the total variance, respectively. Our results contribute to a better understanding of the mechanisms controlling decadal variability of the Indian summer monsoon.